Acesso e permanência na educação superior: uma análise das medidas de acessibilidade e inclusão em tempos de corte dos recursos públicos no período de 2016 a 2020 - Silveira, Ana Carolina Michelon (2021)
This work was developed within the Post Graduate Program in Education of the Federal University of Santa Maria, in the line of research of Special Education, Inclusion and difference. In this study, we investigate the development of the accessibility and permanence actions in the accessibility centers of the Brazilian federal universities in the light of government budget cuts in education, particularly the ones related to the programs Prouni, Reuni and Incluir. We consider the history of higher education in Brazil, the normative framework, and the relationship of special education inside higher education as theoretical framework in order to understand how the higher education process is being built as well as the role of public policy financing for inclusion as an important tool for permanency in higher education, with emphasis on the National Student Assistance Plan (PNAES). We also map scientific production under three main descriptors: “Higher Education Financing”, “Accessibility Center” and “Inclusion in Higher Education”. By means of the state of knowledge (MOROSINI, 2015), we observed that the majority of the analyzed works features inside knowledge about the inclusion process in the researched institutions but the financing of special education within the institutions is of little concern. In this work, a quantitative and qualitative methodological approach is conducted; at first, we perform a quantitative analysis of PNAES budgets within the universities, and thereafter we carry out a qualitative analysis using data collected from narrative interviews that were analyzed using the Content Analysis Technique of Bardin (2011). For this intent, we interviewed supervisors and personnel of Specialized Educational Services from three federal universities located in South Region of Brazil. The results indicate that Specialized Educational Services is not named as such in all institutions, but every institution organizes some sort of support to the students with an educational approach. Finally, we establish that the budget cuts resulted in consequences for the access and permanence measures, being one of the most affected measures the reduction in recruitment of scholarship students within the accessibility centers and in the purchase of accessible teaching material, facts that follow the promulgation of the Constitutional Amendment 95/2016, which hinders the recruitment of personnel to work on the necessities of students with disabilities, making the services provided by the universities precarious.